2000
DOI: 10.1128/iai.68.12.7190-7194.2000
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Expression of Enterococcus faecalis Aggregation Substance Surface Protein Facilitates Bacterial Internalization by Cultured Enterocytes

Abstract: Aggregation substance (AS) is anEnterococcus faecalis surface protein that may contribute to virulence. Using a recently described system for controlled expression of AS in E. faecalis and the heterologous host Lactococcus lactis, experiments were designed to assess the effect of AS on bacterial internalization by HT-29 and Caco-2 enterocytes. AS expression was associated with increased internalization of E. faecalis by HT-29 enterocytes and of L. lactis by HT-29 and Caco-2 enterocytes. Compared to enterocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 26 publications
2
41
0
3
Order By: Relevance
“…In addition to promoting conjugation processes, the presence of AS also increases the ability of enterococci to adhere to host surfaces. The reported increase in uptake of AS-expressing cells into intestinal epithelial cells (20,26,31) suggests the possible involvement of AS in the translocation of E. faecalis from the intestine to the bloodstream. On the other hand, AS of E. faecalis has been implicated as a virulence factor in several model systems (21), and its in vivo induction has recently been demonstrated (17).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to promoting conjugation processes, the presence of AS also increases the ability of enterococci to adhere to host surfaces. The reported increase in uptake of AS-expressing cells into intestinal epithelial cells (20,26,31) suggests the possible involvement of AS in the translocation of E. faecalis from the intestine to the bloodstream. On the other hand, AS of E. faecalis has been implicated as a virulence factor in several model systems (21), and its in vivo induction has recently been demonstrated (17).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that AS promotes the adhesion of E. faecalis to fibrin (24) as well as to the extracellular matrix proteins fibronectin, vitronectin, collagen type I, and thrombospondin (36). In direct interaction with cultured mammalial cells, AS-mediated uptake was demonstrated with intestinal epithelial cells (34,43) and a colon cell line (26). Increased adhesion to renal tubular cells was demonstrated (28).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of Asc10 on the cell surface opens the possibility that only a brief induction event-resulting from a recipient cell or an environmental cue-is necessary to present AS on the surface for a considerable amount of time. This could allow pCF10-containing cells to adhere to different host cell types (31,46,53), to withstand the attack of phagocytic cells (43,50), or to bind to potential enterococcal recipient cells that might only be transiently passing through a particular ecological niche, such as the intestinal lumen. This tethering of potential recipients in close proximity could facilitate a pheromone response by the donor cells, ultimately increasing plasmid transfer.…”
Section: Discussionmentioning
confidence: 99%